MAURITIUS: A CYBER-ISLAND IN THE MAKING. - Ackbarally, Nasseem (Contemporary Review, 2002)
Focuses on the development of information and communication technology in Mauritius. Developments in computer software; Export and import of information technology (IT) services; Set up for IT training.